Legal Aspects of The Use and Protection of Wild Relatives of Cultivated Plants in The Republic of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
The article gives an overview of the legal aspects of the protection of wild relatives of cultivated plants in the Republic of Uzbekistan. Laws and articles aimed at the protection and defense of certain categories of plants and redivid territories are given. Proposals were also made to create a department (department) under the Main Forestry Directorate of the Ministry of Agriculture of the Republic of Uzbekistan for the use and protection of wild relatives of cultivated plants, which would allow the development of market relations between state bodies and the private sector in the field of use and protection of DSCR.